Growth of nano-polycrystalline CuIn1-xAlxSe2 thin films and its photovoltaic cell formation - Rajesh Niranjan; Naresh Padha (Results in Surfaces and Interfaces, 2024)
Nano-polycrystalline thin films of CuIn1-xAlxSe2 (CIAS) chalcopyrite material are re-grown on annealing the 700 nm thick Cu/In/Al/Se stack at temperatures ranging from 523 to 623 K. The stack is obtained at room temperature by sequentially evaporated layer deposition (SELD) technique. The grown films show a tetragonal crystal system of CIAS having unit cell parameters a; b = 5.781(5) Å, c = 11.593 (7) Å, with cell volume (V) = 387.523(4) Å3. The micrographs of the films show grains of spherical and cylindrical shapes. Raman spectra of the layers indicate A1 mode at 180.72(7) cm−1, which confirms the CIAS phase. The thin film's energy dispersive X-ray analysis (EDAX) establishes CuIn0.63Al0.37Se2 stoichiometry at 523 K. The direct allowed bandgap (Eg) value varies between 1.35 and 1.50 eV with a change in TA from 523 to 623 K; the values are near the optimum PV cell. The grown thin film samples exhibit absorption coefficient (α) ≥ 1 × 105 cm−1. The solar cell structure of FTO/p-CIAS/n-CdS/In exhibits a photovoltaic (PV) response.